Omega-3 Fatty Acid Fortification of Flax Through Nutri-Priming - Marques, Edward; Darby, Heather; Kraft, Jana (Frontiers in Nutrition, 2021)
Omega-3 (n-3) fatty acids (FA) play an essential role in human physiology and health. As a result, a variety of n-3 FA-fortified functional foods have become commercially available for human consumption. These fortified functional foods are created through various processes; however, nutri-priming, a potentially promising biofortification approach, has not been utilized to develop plant-based n-3 fortified foods. We sought to determine whether nutri-priming is a viable option to fortify seeds and sprouts with n-3 FA. Additionally, we assessed whether n-3 FA nutri-priming would inhibit germination of the primed seeds. To address these goals, we nutri-primed brown flax in three priming solutions, control (0% fish oil (FO)), 10% FO and a 20% FO solution and determined the FA content and profile of seeds and sprouts and germination percentage of primed seeds. n-3 FA nutri-priming with FO altered the FA profile in seeds and sprouts, with increases in the absolute content of 20:5 n-3, 22:6 n-3, 22:5 n3, 18:4 n-3, and 20:4 n-6. However, n-3 FA nutri-priming did not increase the absolute content of 18:2 n-6, 18:3 n-3, total saturated FA, total monounsaturated FA, total polyunsaturated FA, total n-6 FA, or total n-3 FA. Our results also showed that n-3 nutri-priming decreased the germination percentage of primed seeds, with 10% and 20% FO priming solution reducing germination by 4.3% and 6.2%, respectively. Collectively, n-3 nutri-priming increases the n-3 FA content in plant-based functional foods, however, the process does inhibit germination of primed seeds. Further research utilizing different seed and oil types still needs to be conducted to determine if this is a commercially viable approach.